Presentation of DMF Index in Croatia and Europe - Marijana Radić; Tomislav Benjak; Vlasta DEČKOVIĆ VUKRES; Željko Rotim; Irina FILIPOVIĆ ZORE (University of Zagreb. School of Dental Medicine, 2015)
Dental caries is the most common oral disease affecting all age groups and a major cause of tooth loss. Although a decrease in the prevalence of dental caries has been marked across the globe, in many countries it has remained a major oral-health problem. Aim: The objective of this paper was to show the trends in the DMF index in Croatia, compare it with European countries and present further courses of action oriented towards promotion of oral health and decrease in caries prevalence. Material and Methods: The DMF index databases have been generated based on online database searches for the period from 1985 to 2015. Results: Croatia is one of European countries with a high DMF index relating to 12-year old children (4.18). The experience of countries with a low DMF index has shown that dental caries can be controlled through education and prevention activities, which eventually lead to diminished financial costs, at individual and national level, improving overall health and quality of life. Conclusion: Tracking and monitoring of oral health i.e. dental caries need to be improved in terms of creation of data base systems on the prevalence of dental caries, determining multi-factorial causes of its occurrence and with respect to the implementation of national oral-health prevention programs.